2014
DOI: 10.3947/ic.2014.46.3.209
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus Tracheobronchitis and Influenza A Co-infection in a Patient with AIDS and Neutropenia

Abstract: Aspergillus tracheobronchitis (AT), an unusual form of invasive pulmonary aspergillosis (IPA), is characterized by pseudomembrane formation, ulcer or obstruction that is predominantly confined to tracheobronchial tree. Hematologic malignancies, neutropenia, solid organ transplantation, chronic corticosteroid therapy and acquired immunodeficiency syndrome (AIDS) are known to be major predisposing conditions. However, since the introduction of highly active antiretroviral therapy, there is only one reported case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…In addition to our current cases, we searched the English language published literature using PubMed/Medline with the search terms 'influenza' and 'aspergillus' or 'aspergillosis' from January 2009 to March 2018. 1,[5][6][7][8][9][10][11][12][13][14][15][16][17][18]…”
Section: Cases From the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to our current cases, we searched the English language published literature using PubMed/Medline with the search terms 'influenza' and 'aspergillus' or 'aspergillosis' from January 2009 to March 2018. 1,[5][6][7][8][9][10][11][12][13][14][15][16][17][18]…”
Section: Cases From the Literaturementioning
confidence: 99%
“…Invasive pulmonary aspergillosis (IPA) co-infections with influenza have been sporadically reported in case reports and small case series, [5][6][7] but no systemic research has yet been aimed at investigating the clinical characteristics of IPA coinfections with influenza, how to recognize it earlier and its poor prognostic factors.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the isolation of Aspergillus sp in the immunocompetent host without these conditions may be initially considered as a colonizer or nonpathogen. However, recent cases have suggested that Aspergillus may rapidly lead to invasive disease in the setting of severe influenza infection including among those without classic risk factors [ 3 , 4 ]. The pathogenesis of invasive aspergillosis in this setting may include viral disruption of the respiratory epithelium and impaired local immunity as well as viral-induced systemic Th1/Th2 changes and lymphopenia [ 5 11 ].…”
mentioning
confidence: 99%
“…Although sporadic case reports of invasive aspergillosis in the setting of an influenza infection have been published [ 3 , 4 , 14 ], robust data are sparse, especially among previously immunocompetent hosts. This report describes the occurrence of invasive Aspergillus complicating severe influenza infections among patients admitted to the intensive care unit (ICU) at a large academic hospital during the 2015–2016 influenza season.…”
mentioning
confidence: 99%
“…ITBA is a rare form of invasive pulmonary aspergillosis. In previous reports, immunocompromised patients, such as those who had received organ or bone marrow transplantation, those being treated with immunosuppressive agents such as steroids and those suffering from acquired immu- (6,(10)(11)(12). The symptoms are usually non-specific, such as cough, dyspnea and respiratory failure (9,13,14).…”
Section: Discussionmentioning
confidence: 99%